Influence of age on the outcome of antitumour necrosis factor alpha therapy in rheumatoid arthritis. Issue 9 (17th November 2008) - Radovits, B J; Kievit, W; Fransen, J; van de Laar, M A F J; Jansen, T L; van Riel, P L C M; Laan, R F J M
Abstract : Objective: To investigate the influence of age on the effectiveness and tolerance of antitumour necrosis factor alpha (TNFα) therapy in rheumatoid arthritis (RA). Methods: 730 patients of the Dutch Rheumatoid Arthritis Monitoring (DREAM) register were categorised into three groups according to their age at initiation of anti-TNFα therapy (<45, 45–65 and >65 years). Effectiveness of anti-TNFα therapy was primarily assessed by longitudinal analysis of the DAS28 during the first 12 months of treatment. Results: Improvement in disease activity and physical functioning was significantly less in elderly patients, correcting for relevant confounders. Elderly patients reached the EULAR categories of good responders and remission less often than younger patients. Drug survival, co-medication use and tolerance were comparable between the three age groups. Conclusion: Anti-TNFα therapy significantly reduced disease activity in all age groups of patients; however, it appeared less effective in elderly compared with younger RA patients.